Qualified manpower in engineering : Britain and other industrially advanced countries - Prais, S.J. [Verfasser] (My University, 1989)
"This article examines the numbers of skilled persons in engineering and allied occupations who qualify each year throughout the skill range - from an engineering doctorate to craftsmen and technicians - and compares Britain with other advanced industrial countries. The main quantitative difference between Britain and other countries lies in the numbers qualifying at the level of qualified craftsman; attention is also drawn to an important qualitative difference in practical content and length of university-degree courses in engineering." (author's abstract) ((en)) In dem Beitrag wird ein internationaler Vergleich der Qualifikationsniveaus im Bereich Ingenieurwissenschaften und Technik vorgenommen. Einbezogen sind Grossbritannien, Frankreich, Japan, die USA und die Bundesrepublik Deutschland. Der Vergleich umfasst alle Ebenen formaler Qualifikation. (IAB)
Qualifizierte Arbeitskräfte in den Ingenieurwissenschaften in Grossbritannien und anderen Industrieländern
Keywords: T 4.7 Technik- & Ingenieurwissenschaften; P 2.4 Facharbeiter / Gesellen; G 1.2.3.1 Potenziale; P 2.6 Hochschulabsolventen; Ingenieurwissenschaft; Techniker; Facharbeiter; Qualifikationsniveau; Internationaler Vergleich; Akademiker; Quantitative Angaben